Comparative Study of Facial Morphology Among Two Ethnic Groups of Bangladeshi Students - Chakraborty, Ruma; Bhattacharjee, Pabitra Kumar; Ashrafuzzaman, Md; Biswas, Rajat Sanker Roy (Bangladesh Journal of Anatomy, 2017)
Background: Physical variation between the people of different ethnic groups can be recorded by anthropometry. This study was carried out to establish the anthropometric difference by measuring the facial parameters among Bengali and Chakma school going children. The data of facial parameters provide important information in plastic surgery, aesthetics, nationality study and medical jurisprudence. Methods: It was an observational and cross sectional study, convenient sampling was done to select the 50 Bengali and 50 Chakma school going children, age ranging from 5-16 years old. Data were collected by using standard anthropometric methods with a sliding caliper. Values were expressed as mean ±standard deviation (SD). Student’s T test was used to compare the results. Result: Morphological face height(p=0.001) and upper face height(p=0.003) in female between Bengali & Chakma present highly significant difference but when comparison were done between male of two ethnic groups significant difference was found only in morphological face height(p=0.045).To find out the sexual difference the subject were arranged at three different age groups where the both ethnic population showed statistical significant sexual difference at the age group of 13-16 years but the lower age group had failed to show any significant difference. Conclusion: Different results of facial parameters between the two ethnic groups revealed a clear ethnic difference by face but in case of gender difference, sex had no considerable effect on facial morphology in children. Bangladesh Journal of Anatomy July 2017, Vol. 15, No. 2 , pp. 56-62